Determining a NOAEL for the consortium linking academic and regulatory insights on BPA toxicity (CLARITY-BPA) core study - Melissa Badding; Noor Aly; Kevin Sondenheimer (Frontiers in Toxicology)
The CLARITY-BPA Core Study is the most comprehensive animal study of oral bisphenol A (BPA) exposure to date. Rats were exposed daily, in utero until postnatal day 21 or for the animals’ lifetime. While the study authors concluded that several observations at the highest dose may be BPA treatment-related, a No-Observed-Adverse-Effect Level (NOAEL) has not been proposed in the published reports. Therefore, select endpoints deemed by the study authors to be potentially BPA treatment-related were further evaluated to determine a NOAEL. These include findings in the female reproductive tract and male pituitary gland at the highest dose level (25,000 μg/kg-bw/day). The data were examined for dose-response, relevance, and consistency of findings across study arms and timepoints, histopathological progression, and concordance with the estradiol positive control. Based on our evaluation, some of the female reproductive tract findings are possibly BPA treatment-related. However, there is a lack of consistency between study arms and/or timepoints, no significant dose-response, and a lack of progression to tumors for proliferative findings. Finally, the findings from the Core Study agree with previous high-quality guideline studies which determined that BPA did not pose adverse effects at doses below 25,000 μg/kg-bw/day in rodents. Altogether, some findings from the Core Study may be BPA treatment-related but they should not be considered adverse. Therefore, we hypothesize that the NOAEL from the Core Study is reasonably considered to be 25,000 μg/kg-bw/day.